A experimentação cinética de personagem: os princípios da animação na indústria e seus desdobramentos como catalisadores do potencial artístico do animador - Antonio Cesar Fialho de Sousa (2013)
This thesis examines variations in building experimental dynamics for Character Animation, aiming to investigate that the core of the animator's artistic potential lives in the regency of synthetic motion - defined here as kinetic. The text argues for the kinetic praxis as the animator's creative genesis, regardless of the media arts and technology base used for the aesthetic result of his work. First of all, the animator is able to express himself as an artist through the construction of qualitative movement (or kinetic) as a differential approach. In order to support the research, a methodology is seek to emphasize the usability of the so called the fundamental principles of animation, using them to construct the dynamics involved in movement for animated characters. The study defines the dynamics of basic actions in Character Animation as a structure of potential kinetic experiment, founded upon the conventional guidelines for building movement. For this purpose, categories are proposed to distinguish types of experimental movement with characters, according to the structure of theoretical systematization developed in the research. Thus, one can track how the classical animation methodology always sustains the experiment with newtonian movement for Character Animation. The creation of this typology with the kinetic experiment stimulates animators to understand how alternative dynamics of actions can be analysed by the methodology described in the survey, based on the fundamental principles. Beyond demystifying these experiments with the dynamics of actions for the reader, this thesis aims to motivate other animators/researchers to add their own categories, in order to broaden the parameters of alternative movements for Character Animation.